Gender ideology and career aspirations among students of architecture in Nigeria. (22nd January 2020) - Fulani, Omoyeni; Amole, Dolapo; Adeboye, Albert
Due to lower female enrolment in architecture programs, this study investigated the gender ideology of students of architecture in private universities in South-West Nigeria to gain insight into perceptions that are pervasive among the students with respect to gender. A questionnaire assessing gender ideology was administered to a sample of 378 students (101 females and 277 males). Statistical analysis revealed that the females were more egalitarian than the males in professional and socio-cultural gender ideology. The gender ideology of the students had a significant relationship with the type of career aspired to but not with their intention to practice architecture. This implied that most females in schools of architecture had succeeded in breaking out of traditional gender role stereotypes. It further suggested that as gender roles become more malleable in favour of females, there would be a greater influx of females into the field of architecture in Nigeria.